Social History of Islamic Education Before Prophethood (570-610 AD) - Zuhur Diana; Zulfi Mubaraq; Lintang Ramadhani; Aris Rohmatul Maula (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
The study of the social history of Islamic education before the Prophethood (570-610 AD) is very important to study in more depth. This is because these studies never stop being debated. The aim of this article is to understand 3 things: First, the Islamic education paradigm at that time. Second, the factors that influence it. Third, positive and negative implications for the ignorant society. The method used is library research with an article review approach based on Harold Laswell's theory. Data were collected using literature review procedures and analyzed using content analysis techniques. The results found 3 things: First, there are 5 forms of paradigm: (1) Goal: education as the transmission of religious, social and cultural values ​​(2) Material: ancestral beliefs, tribal traditions, life skills, poetry (3) Method: informal through oral traditions and practices (4) Murshid: tribal leader and poet. (5) Students: Arab society. Second, internal factors: (1) Brave soul (2) Likes to give alms (3) Virtuous. The external factors: (1) Natural conditions (2) Social conditions (3) Cultural acculturation. Third, positive implications: (1) High sense of solidarity (2) Survival skills (3) Development of Arabic literature. Meanwhile, the negative implications: (1) Idolatry (2) Limited access to education (3) Racial, feudal and patriarchal character. The conclusion of this article shows that the social history of Islamic education in the pre-prophetic period had progressed, even though it was simple.